PERBANDINGAN KUAT TEKAN SILINDER TAK TERKEKANG DENGAN CONE INDEKS PADA TANAH DICAMPUR DENGAN SEMEN - Khaizal Jamaluddin (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2014)
Since 1981, Indian geotechnical expert have been introduced shear strength of soil is cone index (CI). Recently, common existing shear strength index in soil mechanic studies such as N-SPT, qc-CPT.However, the cone index (CI) parameter till in this time not yet been made by standard of the testing of soil sample in the soil mechanics laboratory. Pursuant to this problem, we have correlated cone index (CI) with unconfined compression strength (qu). The research used two measurement are unconfined compression and penetration ofcone bar silinder into soil sample. Diameter cone bar penetration is 0.5 cm, high 7 cm and cone angle part of 60 degree. The soil samples for research from Indrapuri sub district, Aceh Besar. For strength variation soil sample mixed cement with content 0%, 3%, 6% and 9% with waiting periode of samples 0, 2 and 4 days. The results of research showed good and strong correlation between cone index (CI) and unconfined compression strength (qu). Parameters with R2 80% from linear comparison.